Study of rock slope stability of formation outcrops in Hamrin Anticline /NE Tikrit. - Abood, Mohammed; Hussain, Abood, Amera; Ali, Jamal (Iraqi Journal of Science, 2024)
This Study aims to engineering geological evaluation of Fatha and Injana Formations in northern Hamrin anticline throughout geological and engineering geological Survey including Preparing engineering geological map (Scale1:90000) and Studying rock Slopes Stability in (6) Stations ,representing all types of failures (taken place and possible).General Survey for rock Slopes included Classification and engineering description according to [1], [2]. The slopes in the area are Classified based on the direction of the Strike Slopes and Strike of beds into Parallel, Oblique Lateral and orthogonal Slopes according to [3].Classification and the Slope Types are Concordant Slope and discordant Slope . The rocks in the area consists of two engineering geological units on basis of unconfined Compressive Strength(which derived from point load test),these units are: 1-Moderately Strong Compressive Strength and 2-Weak-Very Weak Compressive Strength.The main reasons for failures occurring are differential Weathering Which Cause to over hanging Slopes by under Cutting ,using rocks in various purposes and the role of the discontinuities which exist in the rocks..